The Role of Internal Marketing Strategy on the Quality of Frontline Employee Services in Private Higher Education - Sukmono, Machdi; Yasik, Yudi Limbar; Wahyudianty, Melsa Ulfie; Indrayani, Rina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This research examines the influence of internal marketing strategies on the service quality of frontliner employees in private higher education institutions (PHEIs). With increasing competition among PHEIs, the ability of administrative staff to deliver excellent service has become essential in shaping institutional image and student satisfaction. Using a quantitative explanatory research approach, data were collected from 85 frontliner staff at five PHEIs in Bandung through questionnaires. The internal marketing variable was measured using nine indicators including training, rewards, leadership, and work atmosphere, while service quality was assessed through the SERVQUAL model. The results of multiple linear regression analysis indicate that internal marketing has a significant positive effect on service quality (β = 0.634, p < 0.05), with an R² value of 0.493. Among internal marketing dimensions, training and rewards were found to be the most influential in improving responsiveness and assurance. This study suggests that strategic internal marketing practices are critical in enhancing staff motivation, satisfaction, and ultimately, service excellence in higher education.